Porphyrinic Zirconium Metal–Organic Frameworks (MOFs) as Heterogeneous Photocatalysts for PET‐RAFT Polymerization and Stereolithography - Zhang, Liwen; Shi, Xiaobing; Zhang, Zhiheng; Kuchel, Rhiannon P; Namivandi‐Zangeneh, Rashin; Corrigan, Nathaniel; Jung, Kenward; Liang, Kang; Boyer, Cyrille (Angewandte Chemie International Edition, 2021)
In this study, porphyrinic zirconium (Zr) MOFs were investigated as heterogeneous photocatalysts for photoinduced electron transfer‐reversible addition‐fragmentation chain transfer (PET‐RAFT) polymerization of various monomers under a broad range of wavelengths, producing polymers with high monomer conversions, narrow molecular weight distributions, low dispersity and good chain‐end fidelity. Screening of various porphyrinic Zr‐MOFs (Zn) containing Zn‐metalled porphyrinic ligands demonstrated that MOF‐525 (Zn) with the smallest size had the best photocatalytic activity in PET‐RAFT polymerization, due to enhanced dispersion and light penetration. Oxygen tolerance and temporal control were also demonstrated during MOF catalysed PET‐RAFT. Results suggested that the polymerization rates were significantly affected by changing the size and surface area of MOFs, and the heterogeneous MOF photocatalysts could be easily separated and recycled for up to five independent PET‐RAFT polymerizations without an obvious decrease in efficiency. Finally, the MOF photocatalysts were utilized to create three‐dimensional polymeric objects with high resolution via visible light mediated stereolithography in an open‐air environment. Porphyrinic zirconium MOFs act as heterogeneous photocatalysts for photoinduced electron transfer‐reversible addition‐fragmentation chain transfer (PET‐RAFT) polymerization of various monomers under a broad range of wavelengths, producing polymers with high monomer conversions, narrow molecular weight distributions, low dispersity and good chain‐end fidelity